Enemy at the water cooler : real-life stories of insider threats and Enterprise Security Management countermeasures - Contos, Brian T. (Syngress, 2006)
Packed with vivid real-life cases, this comprehensive book addresses the most difficult to manage and costly of all security threats: the insider.